Technological self-efficacy and sense of coherence: Key drivers in teachers' AI acceptance and adoption - Asmahan Masry Herzallah; Rania Makaldy (Computers and Education: Artificial Intelligence)
This study investigates the factors influencing teachers within the Israeli education system toward the adaptations of artificial intelligence (AI) in teaching by examining the roles of technological self-efficacy (TSE) and a sense of coherence (SOC). Drawing on the Technology Acceptance Model (TAM), a sample of 200 Arab and Jewish teachers in Israel completed online questionnaires. The findings indicated a positive attitude towards AI among teachers. We found a significant positive correlation between perceived usefulness, perceived ease of use, and positive attitude towards AI. TSE fully mediated the relationship between attitude towards AI and adoption intentions AI, while a SOC partially mediated the relationship between TSE and teachers' attitude towards AI. The findings underscore the importance of developing TSE and fostering a SOC among teachers as part of the AI implementation process in the education system.The findings offer a new understanding of AI technology adoption processes in education by incorporating psychological variables into the TAM framework and providing practical insights for decision-makers in the Israeli education system and beyond.